2015
DOI: 10.1111/bij.12652
|View full text |Cite
|
Sign up to set email alerts
|

Does a polymorphic species have a ‘polymorphic’ diet? A case study from a lacertid lizard

Abstract: Lizards are ideal for studying colour polymorphism, because some species are polymorphic and the morphs often have different ecological or reproductive strategies. We studied the feeding habits of six polymorphic populations of Podarcis muralis to test whether morphs differed in their diet. Some taxa were selected in a similar way by all morphs, but selection on other taxa varied and was characteristic of each morph. Diet was most different for the red and yellow morphs. Two hypotheses could explain these diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 57 publications
1
24
0
Order By: Relevance
“…We propose that the morphs are ecologically segregated and that their frequencies reflect the amount of available niche space in which the fitness of each morph approaches equality in the appropriate niche. Similar themes have been recently demonstrated in polymorphic lacertid lizards (Scali et al, 2016). Given the very low population numbers of bears on these islands, it seems that inbreeding effects would have compromised long-term persistence without occasional migration from the mainland (Hedrick & Ritland, 2011) as well as fitness differentials between the morphs (Klinka & Reimchen, 2009a).…”
Section: Discussionsupporting
confidence: 73%
“…We propose that the morphs are ecologically segregated and that their frequencies reflect the amount of available niche space in which the fitness of each morph approaches equality in the appropriate niche. Similar themes have been recently demonstrated in polymorphic lacertid lizards (Scali et al, 2016). Given the very low population numbers of bears on these islands, it seems that inbreeding effects would have compromised long-term persistence without occasional migration from the mainland (Hedrick & Ritland, 2011) as well as fitness differentials between the morphs (Klinka & Reimchen, 2009a).…”
Section: Discussionsupporting
confidence: 73%
“…This mechanism also allows morphs to vary in their degree of trophic specialization (e.g. generalist or specialist) as they do in mating behaviour and other physiological traits [ 2 4 , 18 , 29 , 52 54 ]. Our hypothesis synthesizes and expands on the mechanisms proposed by Skúlason & Smith [ 13 ] and Karpestam & Forsman [ 17 ] to explain the evolution of a trophic polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary divergence among morphs is expected to arise via one of two mechanisms [ 17 ]: morph-specific differences in microhabitat exploitation or morphological constraints (e.g. gape limitation) that influence prey selectivity [ 16 , 18 , 19 ]. These two hypotheses differ in that the first proposes that a trophic polymorphism is unrelated to diet selection and instead is a function of differences in prey diversity arising from segregation of morphs among different microhabitats.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies from the Pyrenees describe up to five ventral colour morphs in both adult males and females: white, yellow and orange pure morphs, and white‐orange and yellow‐orange intermediate morphs (Pérez i de Lanuza et al ., ; but see the proposal for a sixth white‐yellow morph in Calsbeek et al ., ; Zajitschek et al ., ). In contrast, studies from Northern Italy describe from four to six morphs and, remarkably, have reported the existence of a red (rather than orange) morph in this area (Sacchi et al ., , , ; Galeotti et al ., ; Scali et al ., , ; Pellitteri‐Rosa et al ., , ). The discrepancy between the orange and the red morphs might indicate some underlying biological meaningful difference (e.g.…”
Section: Introductionmentioning
confidence: 99%